Influence of pole length and stiffness on the energy conversion in pole-vaulting - Ekevad, M.; Lundberg, B. (Journal of Biomechanics, 1997)
An impact process similar to pole-vaulting is studied, viz., the impact in a vertical plane between the bottom end of a slightly curved elastic bar (pole), with a point mass (vaulter) at the top end, and a rigid support (pole box). Before impact, the velocity of the pole and the vaulter forms a certain angle (take-off) with the horizontal ground. Finite element calculation of the trajectories of the vaulter are carried out, and a performance figure, defined as the ratio between the maximum potential energy of the vaulter and the initial kinetic energy of the vaulter and the pole, is determined as a function of dimensionless parameters. As the vaulter remains passive during the vault, in contrast to a real vaulter, this performance figure is also the efficiency of conversion of the initial kinetic energy to the achieved potential energy in the vault. It is shown that, under normal pole-vault conditions, there exists a maximum performance figure with respect to pole length and stiffness. For an initial velocity and a body mass which are representative of an elite pole-vaulter, the maximum performance figure 0.87 is obtained for a pole with length 5.5 m.